Method for researching relationship between hollow powder rate of powder and density of additive product
By using high-resolution industrial CT and a multinomial regression model, the problem of quantitative assessment of the void ratio and density of metal powder was solved, providing theoretical support for product quality prediction and process optimization.
Patent Information
- Application Number
- CN202510988201.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-17
- Publication Date
- 2025-10-28
AI Technical Summary
Existing technologies make it difficult to quantitatively assess the relationship between the void ratio of metal powder and the density of laser selective melting products, leading to difficulties in product quality prediction and process optimization.
High-resolution industrial CT technology is used for three-dimensional visualization analysis. Combined with Archimedes' weighing and displacement method and the gas specific gravity bottle method, a quantitative evaluation method for the hollowness of metal powder and the density of additive products is established. A quantitative mapping model is established through a multinomial regression model.
It enables accurate assessment of the void ratio of metal powder and the density of laser selective melting formed products, providing a theoretical basis for quality prediction and process optimization.
Smart Images

Figure CN120839083A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of additive manufacturing technology, specifically relating to a method for studying the relationship between the hollow powder ratio of powder and the density of additive products. Background Technology
[0002] Selective laser melting (SLM) is an additive manufacturing technology for metal materials based on powder bed deposition. First, the CAD model of the part is sliced into layers. Using a pre-deposition method, a scanning galvanometer drives a laser beam, under computer control, to scan the selected area of the alloy powder layer along a graphic trajectory. This melts and deposits a thin metal layer with the same thickness as the slice and a shape resembling a cross-section of the part, until a metal part identical to the CAD model of the component is manufactured. With the increasing demands for quality consistency and internal defect control in high-performance structural components, SLM places higher requirements on the microstructure of the raw material powder. For typical metal powders, the mechanical properties after SLM formation are highly dependent on the density and micropore defect distribution of the formed body. Hollow powder in the raw material becomes a key potential factor affecting the density of the product.
[0003] The void ratio of metal powder has a significant impact on the density of laser selective melting (LSM) formed products. Hollow or porous powder particles reduce the packing density of the powder bed and introduce pores during melting, leading to a decrease in the density of the final part. Controlling the void ratio of the powder and optimizing its morphology and particle size distribution are key to ensuring high density in LSM formed products.
[0004] Currently, research on the quantitative identification of hollow metal powder ratio and its direct correlation with the density of products formed by selective laser melting (SLM) remains limited. Although some literature has attempted to reveal the influence of hollow metal powder on forming defects based on metallographic sections or density methods, these methods are difficult to implement for large-scale, three-dimensional visualization analysis. The advent of high-resolution industrial CT technology has enabled non-destructive and precise tracking of the internal cavity structure of powder particles and the evolution of pores in formed parts, providing a feasible path for establishing a quantitative assessment of the relationship between hollow metal powder ratio and the density of SLM products.
[0005] Therefore, there is an urgent need to develop a systematic approach based on high-resolution industrial CT that can quantitatively assess the relationship between the void ratio of metal powder and the density of laser selective melting formed parts, thereby providing a theoretical basis and practical support for the quality prediction and process optimization of additive manufacturing products. Summary of the Invention
[0006] The purpose of this invention is to provide a method for studying the relationship between the hollow powder ratio and the density of additive products, so as to solve the problems mentioned in the background art.
[0007] To achieve the above objectives, the present invention provides the following technical solution: a method for studying the relationship between the hollow powder ratio of powder and the density of additive products, the specific steps of which include: step S1: preparing metal powders with different hollow powder ratios;
[0008] Step S2: Prepare the sample using a laser selective melting forming process with the same parameters;
[0009] Step S3: Perform CT detection on each group of printed samples in step S2 to obtain the density of samples with different metal powder hollow powder ratios.
[0010] Step S4: Establish an evaluation relationship between the hollow powder ratio of the metal powder sample and the density of the additively manufactured product;
[0011] Step S5: Calculate cross-validation and error assessment schemes to verify the accuracy and repeatability of CT analysis;
[0012] Step S6: Combine error analysis to clarify the relationship between the hollow powder ratio of metal powder and the density of additive manufacturing products.
[0013] Preferably, in step S1, when preparing the metal powder sample, five groups of metal powders are prepared using conventional vacuum degassing and optimized atomization. The hollow powder ratios of the five groups of metal powders are controlled to be 1%, 5%, 10%, 15%, and 20%, respectively. While detecting the hollow powder ratio of each group of metal powders using industrial CT, the particle size distribution, flowability, sphericity, and tap density parameters of the metal powders are recorded. Parameters other than the hollow powder ratio are controlled to avoid other parameters affecting the final forming density.
[0014] Preferably, in step S2, when preparing samples using laser selective melting forming process, all batches of samples should maintain the same printing parameters and component design, only changing the metal powder with different void fractions; fix the laser power, scanning speed, layer thickness, single-layer scanning strategy and filling strategy to ensure that the variables of each group of forming process are consistent; print five sets of cylindrical test blocks with a diameter of 5mm and a height of 20mm for each batch of powder to ensure that the scanning conditions are repeatable, use the same scanning path and interlayer offset to ensure that the density difference of the final sample is only caused by the void fraction of the powder.
[0015] Preferably, in step S3, the acquired CT projection data is reconstructed in three dimensions using industrial CT software, and the reconstructed volume data is automatically segmented using a pore and inclusion analysis module; the total pore volume, surface area, and porosity parameters are calculated using voxel statistics to calculate the local pore density for each functional area; a 3D defect model is generated to visually observe the pore morphology and spatial distribution, and the defect size is statistically analyzed, finally obtaining and recording the density of each group of samples.
[0016] Preferably, in step S4, the macroscopic density of the sample is measured using the Archimedes weighing and displacement method, and the true density of the powder is measured using the gas specific gravity bottle method in combination with the density parameters of the sample obtained in step S3, and the theoretical density is evaluated by comparing with the density of the metal powder matrix; finally, the relationship between hollow powder ratio, microscopic density and macroscopic density is established using statistical and physical modeling methods.
[0017] Preferably, in step S5, the sample from step S2 is selected for metallographic testing. The pore location and morphology measured by metallography are compared with the CT results to evaluate the CT's ability to detect the number and size of pores. Multiple samples are prepared repeatedly under the same powder and process conditions, and the density and porosity of each sample are detected using the same CT and analysis procedure. The standard deviation and confidence interval of the results are calculated to evaluate the reliability and consistency of the method. The difference between the CT porosity and the Archimedes method measurement is compared to quantify the error introduced by the tiny pores that the CT may miss.
[0018] Preferably, in step S6, the relationship between the hollow powder ratio of metal powder and the density of additive manufacturing products is clarified by combining the error analysis of step S5. The relationship between the hollow powder ratio and density and porosity characteristics of powder is compared by combining experimental data. A quantitative model is established by using regression analysis to provide technical support for the application of additive manufacturing technology.
[0019] Compared with the prior art, the beneficial effects of the present invention are:
[0020] This invention establishes a quantitative mapping model for the evolution of the void ratio of existing metal powder and the density of products after selective laser melting. It overcomes the problems of lack of three-dimensional visualization of micropore morphology identification and evolution mechanism and lack of systematic evaluation methods for the void ratio of metal powder and product density, thus providing a theoretical basis and practical support for the quality prediction and process optimization of additive manufacturing products. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of the method flow of the present invention;
[0022] Figure 2 The metal powders of different hollow powders prepared for the samples in this embodiment were analyzed by CT method.
[0023] Figure 3 Metallic powders from different hollow powders prepared for the samples in this embodiment were analyzed using metallographic methods to determine their patterns.
[0024] Figure 4 Images of laser selective melting forming process samples prepared using the same parameters in this embodiment;
[0025] Figure 5 The sample density in this embodiment was determined using the CT method.
[0026] Figure 6 The metallographic pattern was used to determine the sample density in this embodiment. Detailed Implementation
[0027] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0028] Example
[0029] See also Figure 1 and Figure 6 The present invention provides a technical solution: a method for studying the relationship between the hollow powder ratio of powder and the density of additive products, the specific steps of which include: step S1: preparing metal powders with different hollow ratios;
[0030] Step S2: Prepare the sample using a laser selective melting forming process with the same parameters;
[0031] Step S3: Perform CT detection on each group of printed samples in step S2 to obtain the density of samples with different metal powder hollow powder ratios.
[0032] Step S4: Establish an evaluation relationship between the hollow powder ratio of the metal powder sample and the density of the additively manufactured product;
[0033] Step S5: Calculate cross-validation and error assessment schemes to verify the accuracy and repeatability of CT analysis;
[0034] Step S6: Combine error analysis to clarify the relationship between the hollow powder ratio of metal powder and the density of additive manufacturing products.
[0035] In this embodiment, preferably, in step S1, when preparing the metal powder sample, five groups of metal powders are prepared by conventional vacuum degassing and optimized atomization. The hollow powder ratios of the five groups of metal powders are controlled to be 1%, 5%, 10%, 15%, and 20%, respectively. While detecting the hollow powder ratio of each group of metal powders by industrial CT, the particle size distribution, flowability, sphericity, and tap density parameters of the metal powders are recorded. The parameters other than the hollow powder ratio are controlled to avoid other parameters affecting the final forming density.
[0036] In this embodiment, preferably, in step S2, when preparing samples using laser selective melting forming process, all batches of samples should maintain the same printing parameters and component design, only changing the metal powder with different void fractions; fix the laser power, scanning speed, layer thickness, single-layer scanning strategy and filling strategy to ensure that the variables of each group of forming process are consistent; print five sets of cylindrical test blocks with a diameter of 5mm and a height of 20mm for each batch of powder to ensure that the scanning conditions are repeatable, use the same scanning path and interlayer offset to ensure that the density difference of the final sample is only caused by the void fraction of the powder.
[0037] In this embodiment, preferably, in step S3, the collected CT projection data is reconstructed using industrial CT software to reconstruct the three-dimensional volume, and the reconstructed volume data is automatically segmented using the pore and inclusion analysis module; the total pore volume, surface area, and porosity parameters are calculated using the voxel statistical method, and the local pore density is calculated for each functional area; by generating a 3D defect model, the pore morphology and spatial distribution are observed intuitively, and the defect size is statistically analyzed, and finally the density of each group of samples is obtained and recorded.
[0038] In this embodiment, preferably, in step S4, the macroscopic density of the sample is measured using the Archimedes weighing and displacement method, and combined with the density parameters of the sample obtained in step S3, the true density of the powder is measured using the gas specific gravity bottle method, and the theoretical density is evaluated by comparing it with the density of the metal powder matrix; finally, the relationship between hollow powder ratio, microscopic density and macroscopic density is established using statistical and physical modeling methods.
[0039] In this embodiment, preferably, in step S5, the sample from step S2 is selected for metallographic testing. The pore location and morphology measured by metallography are compared with the CT results to evaluate the CT's ability to detect the number and size of pores. Multiple samples are prepared repeatedly under the same powder and process conditions, and the density and porosity of each sample are detected using the same CT and analysis process. The standard deviation and confidence interval of the results are calculated to evaluate the reliability and consistency of the method. The difference between the CT porosity and the Archimedes method measurement is compared to quantify the error introduced by the tiny pores that the CT may miss.
[0040] In this embodiment, preferably, in step S6, the relationship between the hollow powder ratio of metal powder and the density of additive manufacturing products is clarified by combining the error analysis of step S5. The relationship between the hollow powder ratio and density and porosity characteristics of powder is compared by combining experimental data. A quantitative model is established by using regression analysis to provide technical support for the application of additive manufacturing technology.
[0041] A multinomial regression model was used to establish the relationship between the hollow metal powder ratio and the density of additively manufactured products. Metal powders with hollow powder ratios of 1%, 5%, 10%, 15%, and 20% were denoted as H1, H2, H3, H4, and H5, respectively, and the corresponding results of the density of additively manufactured products detected by the CT method were denoted as D1, D2, D3, D4, and D5.
[0042] A cubic polynomial regression model was used for fitting, and the mathematical expression of the cubic model is D(H)=a+bH+cH 2 .
[0043] After calculating the corresponding coefficients a, b, and c, the relationship between the hollow metal powder ratio and the density of additively manufactured products is established. After establishing the regression analysis model, the degree of model fit is determined using the coefficient of determination Rw of the fit deflection. 2 The calculation formula is: Generally, when the coefficient of determination is 0.7 << R 2 When << 1, it indicates that the established regression model between the metal hollow powder ratio and the density of additive manufacturing products has practical engineering significance.
[0044] Simultaneously, a piecewise regression analysis theorem model can be established to determine the relationship between the hollow powder ratio of metal powder and the density of additive manufacturing products in different intervals.
[0045] Although embodiments of the invention have been shown and described in detail above, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for studying the relationship between the hollow powder ratio and the density of additive products, characterized in that: The specific steps include: Step S1: Prepare metal powders with different void ratios; Step S2: Prepare the sample using a laser selective melting forming process with the same parameters; Step S3: Perform CT detection on each group of printed samples in step S2 to obtain the density of samples with different metal powder hollow powder ratios. Step S4: Establish an evaluation relationship between the hollow powder ratio of the metal powder sample and the density of the additively manufactured product; Step S5: Calculate cross-validation and error assessment schemes to verify the accuracy and repeatability of CT analysis; Step S6: Combine error analysis to clarify the relationship between the hollow powder ratio of metal powder and the density of additive manufacturing products.
2. The method for studying the relationship between the hollow powder ratio and the density of additive products according to claim 1, characterized in that: In step S1, when preparing metal powder samples, five groups of metal powders are prepared using conventional vacuum degassing and optimized atomization. The hollow powder ratios of the five groups of metal powders are controlled to be 1%, 5%, 10%, 15%, and 20%, respectively. While detecting the hollow powder ratio of each group using industrial CT, the particle size distribution, flowability, sphericity, and tap density parameters of the metal powders are recorded. Parameters other than the hollow powder ratio are controlled to avoid other parameters affecting the final forming density.
3. The method for studying the relationship between the hollow powder ratio and the density of additive products according to claim 2, characterized in that: In step S2, when preparing samples using laser selective melting forming process, all batches of samples should maintain the same printing parameters and component design, only changing the metal powder with different void fractions; fix the laser power, scanning speed, layer thickness, single-layer scanning strategy and filling strategy to ensure that the variables of each group of forming process are consistent; print five sets of cylindrical test blocks with a diameter of 5mm and a height of 20mm for each batch of powder to ensure that the scanning conditions are repeatable, use the same scanning path and interlayer offset to ensure that the density difference of the final sample is only caused by the void fraction of the powder.
4. The method for studying the relationship between the hollow powder ratio and the density of additive products according to claim 3, characterized in that: In step S3, the collected CT projection data is reconstructed in three dimensions using industrial CT software. The reconstructed volume data is automatically segmented using a pore and inclusion analysis module. The total pore volume, surface area, and porosity parameters are calculated using voxel statistics to calculate the local pore density for each functional area. By generating a 3D defect model, the pore morphology and spatial distribution are observed intuitively, and the defect size is statistically analyzed. Finally, the density of each group of samples is obtained and recorded.
5. The method for studying the relationship between the hollow powder ratio and the density of additive products according to claim 4, characterized in that: In step S4, the macroscopic density of the sample is measured using the Archimedes weighing and displacement method, and the true density of the powder is measured using the gas specific gravity bottle method in combination with the density parameters of the sample obtained in step S3. The theoretical density is evaluated by comparing it with the density of the metal powder matrix. Finally, the relationship between hollow powder ratio, microscopic density and macroscopic density is established using statistical and physical modeling methods.
6. The method for studying the relationship between the hollow powder ratio and the density of additive products according to claim 5, characterized in that: In step S5, the sample from step S2 is selected for metallographic testing. The pore location and morphology measured by metallography are compared with the CT results to evaluate the CT's ability to detect the number and size of pores. Multiple samples are prepared repeatedly under the same powder and process conditions. The density and porosity of each sample are detected using the same CT and analysis process. The standard deviation and confidence interval of the results are calculated to evaluate the reliability and consistency of the method. By comparing the difference between CT porosity and Archimedes' method measurements, the error introduced by tiny pores that CT may miss is quantified.
7. The method for studying the relationship between the hollow powder ratio and the density of additive products according to claim 6, characterized in that: In step S6, the relationship between the hollow powder ratio of metal powder and the density of additive manufacturing products is clarified by combining the error analysis of step S5. The relationship between the hollow powder ratio and density and porosity characteristics of powder is compared by combining experimental data. A quantitative model is established by regression analysis to provide technical support for the application of additive manufacturing technology.